Investigation of the extraction process in gel‐spinning technology for ultrahigh‐molecular‐weight polyethylene fibers by low‐field nuclear magnetic resonance. Issue 23 (24th February 2015) - Chen, Meijuan; Jiang, Binbo; Wang, Jingdai; Yang, Yongrong; Stapf, Siegfried; Mattea, Carlos; Gong, Qingxia
ABSTRACT A portable, low‐field nuclear magnetic resonance scanner, the nuclear magnetic resonance mobile universal surface explorer, is introduced as a tool for investigating the extraction process of mineral oil in the gel‐spinning technology of ultrahigh‐molecular‐weight polyethylene (UHMWPE) fibers. Factors affecting the extraction process were studied systematically; these included the UHMWPE type, extraction agent type, and concentration and ultrasound. We found that the extraction process could be described by a replacement–dilution dual‐effect model. The extraction agent not only replaced and extracted the mineral oil but also considerably decreased the viscosity of mineral oil and thus enhanced the molecular motion and diffusion of mineral oil. Although chloroform had a smaller molecular size and lower boiling point, benzene and cyclohexane were found to exhibit more efficient extraction and dilution effects on mineral oil. The extraction efficiency could be characterized by the diffusion of mineral oil in the mineral oil/UHMWPE gel/deuterated extraction agent multicomponent systems during the extraction. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42018.